Neighborhoods and health during the transition to adulthood: A scoping review. (May 2020) - Bishop, Asia S.; Walker, Sarah C.; Herting, Jerald R.; Hill, Karl G.
Abstract: Research suggests that neighborhoods play an important role in shaping health outcomes across the life course, but the neighborhood-health link during the transition to adulthood period (18–29 years) is not well studied. A scoping review of 24 studies used thematic analysis to examine the theoretical and methodological approaches of the neighborhood-health literature during this period. Themes illustrate the varied approaches used in this research, including diversity in how neighborhood is defined, theoretical variation regarding the importance of the transition period and the neighborhood-health link, and the importance of gender and race/ethnicity to this area of study. While the literature on this topic is fragmented, with varied definitions and minimal theoretical coherence, all studies found some degree of support for the relationship between neighborhoods and health during the transition to adulthood. Our analysis suggests that future research should focus on developing a theoretical foundation for these relationships in order to clarify key concepts and advance a science to better understand how and why neighborhoods affect health during this period. Highlights: Neighborhoods are linked to health during critical periods in the life course. The neighborhood-health link during the transition to adulthood remains unclear. A scoping review identified current theories and methods used and research gaps. Theory development is needed to clarify the neighborhood-health link and advance study. Incorporate transition experiences and expanded neighborhood and identity measures.